Soil phosphate fractions and microbial biomass in native forest and horticultural areas - Tatiana Suzin Lazeris; Jéssica Pereira de Souza; Fabiane Machado Vezzani; Caroline Lima de Matos; Glaciela Kaschuk (Colloquium Agrariae, 2021)
This study was carried out to verify if the different phosphate fractions in the soil affect the soil microbial biomass. Soil samples were collected from native forest and horticultural areas, in four municipalities in the Metropolitan Region of Curitiba, Brazil, and evaluated for: carbon (C), nitrogen (N) and phosphorus (P) of microbial biomass (MBC, MBN and MBP, respectively), total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), inorganic phosphorus (iP), organic phosphorus (oP) and available phosphorus (aP. Soil suspensions diluted at 10-4 were spread on plates and phosphate solubilizing bacteria (PSB) were counted. The analyses showed that horticultural areas soils accumulated 43% more TP whereas they lost 23% of TOC and 19% of TN comparing to native areas. 69% of TP in the native areas was organic (oP) whereas 59% of TP in the horticultural areas was inorganic (iP). Horticultural areas had lower numbers of colony forming unities of PSB than native areas.  PSB was positively correlated with the ratio of MBC to TOC (qMic), which in turn, was negatively correlated with TOC and TN. Changes in the soil oP fraction suggested a shift in the soil community bacterial structure and in the values of soil microbial biomass, which may have contributed to lower soil organic matter in the horticultural areas.